A Coupled multiphase transport and reaction model for landfill gas emission a case study of Quezon City controlled dumping facility (Payatas Dumpsite) - Vongdalone Vongsikeo
The release of greenhouse gases from waste disposal sites is one of the major contributors of the increase of climatic gases in the atmosphere. Improvement of the existing landfill gas (LFG) emission models is still needed to have better estimates of the amount of landfill gas emitted into the atmosphere, and to develop the most optimal method to control landfill gas emissions. In this study, a one-dimensional transient multiphase transport model of gas, water, solute and heat in a landfill coupled with a reaction model was done to describe the production, transport and emission of methane (CH₄) and carbon dioxide (CO₂) along a profile within both waste layer and soil cover in a landfill. Biodegradation of waste organics was modeled in the waste layers while oxidation of methane was modeled in the soil cover. The set of transport equations was sequentially solved using finite difference method with upwinding scheme to eliminate the numerical dispersion of convection dominated trasport. temperature and pH feedback loops were included to adjust the physical parameters and biological parameters such as growth rate of microbial organisms. Sensoitivity analysis was applied to determine which of the parameters has a significant effect on the transport and reaction processes. The developed model was validated using the results reported in literature and measurements collected at the Quezon City Controlled Dumping Facility (Payatas Dumpsite). The developed LFG model can be further improved and used as a prediction tool in a long term monitoring of methane gas generation and emission from waste disposal sites.